A case of repetitive seizures following immune checkpoint inhibitor therapy as a feature of autoimmune encephalitis. Issue 5 (16th November 2021) - Takebayashi, Yoshiko; Neshige, Shuichiro; Hayashi, Tetsutaro; Aoki, Shiro; Ueno, Hiroki; Iida, Koji; Maruyama, Hirofumi
Abstract: Pembrolizumab, an immune‐checkpoint inhibitor (ICI), is a humanized monoclonal antibody that binds to programmed cell death‐1 receptor (PD‐1) and thereby inhibits binding to its ligand, which inhibits the suppression of activated T cells by cancer cells, resulting in enhancing antitumour immunity. Although several cases of encephalitis have been reported as immune‐related adverse effects of ICIs, epilepsy has not been reported following ICI treatment. We describe the case of an elderly woman with bladder carcinoma who experienced two episodes of generalized seizures after treatment with pembrolizumab. The episodes were atypical of encephalitis, because the seizures were completely responsive to AEDs and the CSF parameters normalized completely without immunotherapy. Since interictal EEG revealed persistent epileptic discharges after the seizures, pembrolizumab was considered to have induced a chronic state of epileptogenicity as the possible pathology, with a clinical picture similar to that of autoimmune epilepsy. The possibility that ICIs may cause an immune‐related adverse effect, such as a chronic epileptic condition, should be considered, since ICIs are used widely.